UTILIZATION OF GRANITE POWDER IN CEMENT MORTAR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The world is struggling with the problem of solid waste disposal. Such materials are causing pollution and damages related to it. The industry of dimensional granite stone has contributed to the development of major environmental problems due to waste generation at different stages of mining and processing operations. The complete process involved with granite starting from mining till the finished product contributes to around 60-80% of the worked masses of the mineral mined, the sludge generated being estimated over 30% of the volume of the sawn block. For dealing with the problem of waste generated by the granite production industry, studies are being conducted for the incorporation of granite sludge as partial or complete replacement of aggregates in cement concrete. This paper elaborates on the study conducted to test the compressive strength, flexural strength, pull-off strength, abrasion resistance, drying shrinkage, air and water permeability, rapid chloride permeability, alkalinity and resistance to sulphate attack in concrete specimen.